REATOR DE LEITO ESTRUTURADO COM AERAÇÃO INTERMITENTE PARA TRATAMENTO COMBINADO DE ESGOTO SANITÁRIO E PÓS TRATAMENTO DE EFLUENTE DE RALF - Oliveira, João Guilherme Baggio de (2016)
The dumping of untreated effluents into water bodies can cause serious damage to the environment. Eutrophication, a phenomenon caused by the release of nutrients such as nitrogen and phosphorus, is one of those damages. Their occurrence promotes excessive growth of algae, decreased dissolved oxygen concentration. The conventional nitrogen removal processes employ two stages physically separated to nitrification and denitrification, which increases construction costs and operation of the process. Research has shown that some reactors models are efficient for simultaneous removal of chemical oxygen demand (COD) and total nitrogen (NT). In this sense, the objective of this study was to evaluate a bed reactor structured with intermittent aeration in the removal of COD and NT sewage untreated combined with effluent RALF. Worked with hydraulic retention time (HRT) fixed in 12 hours and recirculation flow (Qr) of the effluent 3, 2 and 1 to the input flow. Worked up with three times aeration: 33%, 50% and 100% of the time. The affluent used was composed of a fraction of 50% of sewage untreated and 50% of effluent from a reactor Anaerobic Fluidized Bed (RALF). The results indicated that there was no statistical difference between the COD removal rates, regardless of the value of Qr and the reactor aeration time. The COD value obtained for the reactor effluent ranged between 27 and 68 mg.L-1. Values of Total Kjeldahl Nitrogen (TKN) affluent ranged between 40 and 52 mg L-1. Obtained removal rate NT of 50 to 78%, effluent generated treated with N-NH4+ content between 0.7 and 7.1 mg.L-1. We observed the occurrence of nitrification and denitrification Simultaneous (NDS) as oxidized forms were detected (nitrite and nitrate) and reduced (N -NH4) nitrogen at all stages studied. It was concluded that the bed reactor structured with intermittent aeration is effective in joint COD removal and sewage nitrogen